WPŁYW NOWYCH MEDIÓW NA OTAKU JAKO SUBKULTURĘ I SPOŁECZNOŚĆ FANOWSKĄ. ANALIZA NA PRZYKŁADZIE FACEBOOKA - Rybacka, Aleksandra (Civitas et Lex, 2018)
In this paper the author focuses mainly on the impact of new media on young people – members of subcultures and fan communities. The first part is about the general phenomenon of new media, what includes convergence culture and remix culture. Second part contains information about popculture and its creations – subcultures and fan communities. The author explains here why otaku are a subculture. Third part is about the impact of new media on otaku what is analyzed on Facebook example.